2016
DOI: 10.1021/acs.jafc.6b01722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytosterols on the Crystallization Behavior of Oil-in-Water Milk Fat Emulsions

Abstract: Milk has been used commercially as a carrier for phytosterols, but there is limited knowledge on the effect of added plant sterols on the properties of the system. In this study, phytosterols dispersed in milk fat at a level of 0.3 or 0.6% were homogenized with an aqueous dispersion of whey protein isolate (WPI). The particle size, morphology, ζ-potential, and stability of the emulsions were investigated. Emulsion crystallization properties were examined through the use of differential scanning calorimetry (DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…After heating, the WPI solution was mixed with Milli-Q water at 70 °C to create a 1% protein solution. This process, as employed previously, was utilised to minimise denaturation of the whey protein caused by excessive heating or high temperatures (McClements, 2004;Zychowski, et al, 2016).…”
Section: Preparation Of Bulk and Emulsion Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…After heating, the WPI solution was mixed with Milli-Q water at 70 °C to create a 1% protein solution. This process, as employed previously, was utilised to minimise denaturation of the whey protein caused by excessive heating or high temperatures (McClements, 2004;Zychowski, et al, 2016).…”
Section: Preparation Of Bulk and Emulsion Samplesmentioning
confidence: 99%
“…In this equation, a is the maximum height of the diffracted peak, b is the peak position, and c is the full width at half-maximum (FWHM) of the peak, as used previously for SAXS/WAXS analysis (Zychowski, et al, 2016).…”
Section: Synchrotron X-ray Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable efforts have been recently dedicated to improving the solubility and/or bioavailability of phytosterols. So far, chemoenzymatic modifications (He et al., ), emulsion formulations (Fisher, Wachtel, Aserin, & Garti, ; Leong et al., ; Moschakis, Dergiade, Lazaridou, Biliaderis, & Katsanidis, ; Ribeiro et al., ; Rozner, Aserin, Wachtel, & Garti, ; Zychowski et al., ), formation of colloidal phytosterols by precipitation from organic solvents (Rossi, Seijen ten Hoorn, Melnikov, & Velikov, ), synthesis of cyclodextrin inclusion complexes (Meng, Pan, & Liu, ), cocrystallization of phytosterols and triacylglycerols (Acevedo & Franchetti, ), and microencapsulation by spray drying (Di Battista, Constenla, Ramírez‐Rigo, & Piña, ) have been used for decreasing the particle size and improving the solubility of phytosterols. However, long complicated chemical modifications, the use of toxic organic solvents and nonfood grade surfactants remain major obstacles with these methods.…”
Section: Introductionmentioning
confidence: 99%
“…So far, little research has been reported to improve the solubility of phytosterols in water. Recently, some scholars attempted to improve the dispersity or solubility of phytosterols in water via a physical route (Cowins, Abimbola, Ananaba, Wang, & Khan, 2015;Leong et al, 2011;Zychowski et al, 2016). Leong et al (2011) demonstrated the feasibility of phytosterol nanodispersions production using an emulsification-evaporation technique and the particle sizes were about 50 nm.…”
Section: Introductionmentioning
confidence: 99%